THE INFLUENCE OF TRUSTWORTHINESS, PERCEIVED EXPERTISE AND PARASOCIAL RELATIONSHIP ON PURCHASE INTENTION FOR SOMETHINC BRAND COSMETIC PRODUCTS AT TIKTOK SHOP BY THE PEOPLE OF LHOKSEUMAWE CITY - Nurlita Ahwalia; T. Edyansyah; Naufal Bachri; Agustinawati (RADJA PUBLIKA, 2024)
The uniqueness of each social media platform creates creative and innovative marketing methods, using the characteristics of a social media platform, where product marketers can adapt content to suit consumer needs. People's needs and lifestyles are becoming more diverse day by day, one of which is the need to care for themselves through cosmetic products. The development of the times has resulted in more and more cosmetic products appearing. This research aims to determine the influence of trustworthiness, perceived expertise and parasocial relations on purchase intention for Somethinc brand cosmetic products at the Tiktok Shop by the people of Lhokseumawe City. This type of research is quantitative research with the community population in Lhokseumawe City. Respondents totaled 100 people, taken using purposive sampling technique. The data source comes from primary data obtained through distributing questionnaires. The data analysis techniques used are descriptive analysis methods and multiple linear regression analysis, classical assumption tests, instrument tests (validity and reliability), hypothesis tests and coefficients of determination as well as correlation tests and analyzed with the help of the SPSS 23 application program. The results of the research show that simultaneously trustworthiness, perceived expertise and parasocial relations have a positive and significant effect on purchase intention for Somethinc brand cosmetic products at the Tiktok Shop by the people of Lhokseumawe City. Partially, trustworthiness, perceived expertise and parasocial relations also have a positive and significant effect on the purchase intention of Somethinc brand cosmetic products by the people of Lhokseumawe City. Perceived expertise is the variable that most dominantly influences purchase intention with a value of 7,895